Peranan Platform Food Delivery Service dalam Mendukung Marketing Mix UKM di Masa New Normal - Taufik Taufik; Ali Masjono; Irwan Kurniawan; Karno Karno (Jurnal Pengembangan Wiraswasta, 2020)
Platform food delivery service merupakan salah satu bentuk digital marketing yang diterapkan oleh sebagian UKM bisnis kuliner. Penelitian ini menguraikan peranan platform food delivery service dalam mendukung 8 aspek stimulus perusahaan (marketing mix) bisnis kuliner UKM di masa new normal. Metode yang digunakan melalui pendekatan kualitatif deskriptif. Data yang digunakan bersumber dari data sekunder hasil observasi lapangan dan dokumentasi. Objek penelitian terdiri dari vendor Grabfood dalam menampilkan layanan terhadap 25 merchant UKM bisnis kuliner yang telah mengadopsi kemitraan food delivery service Grabfood di masa new normal. Penelitian diadakan pada Maret sampai Juli 2020 di kota Depok. Hasil analisis menunjukkan bahwa platform food delivery service telah berperan dalam mendukung 8 aspek marketing mix yaitu Product, Price, Place, Promotion, Physical Evidence, Process, Probe.Kata kunci: Food delivery service; digital marketing, kinerja bisnis, marketing mix, UKM The Role of the Food Delivery Service Platform in Supporting the SME’s Marketing Mix in the New Normal PeriodABSTRACTThe food delivery service platform is a form of digital marketing implemented by some culinary business SMEs. This study describes the role of the food delivery service platform in supporting 8 aspects of the corporate stimulus (marketing mix) of the SME culinary business in the new normal. The method used is a descriptive qualitative approach. The data used comes from secondary data from field observations and documentation. The research object consists of Grabfood vendors in displaying services to 25 culinary business SME merchants who have adopted the Grabfood food delivery service partnership in the new normal era. The research was held from March to July 2020 in the city of Depok. The analysis results show that the food delivery service platform has played a role in supporting 8 aspects of the marketing mix, i.e. Product, Price, Place, Promotion, Physical Evidence, People, Process, Probing.Keywords: Food delivery service; digital marketing, business performance, marketing mix, SMEs